Dinamika Green Marketing dan Adopsi Keuangan Digital pada Sektor Bisnis: Suatu Tinjauan Literatur - Ascasaputra Aditya; Utami Tunjung Sari; Bhenu Artha; Bahri Bahri; Niken Permata Sari; Antonius Satria Hadi; Cahya Purnama Asri (Rashid : Journal of Economic, 2026)
The primary objective of this study is to identify the strategic role of FinTech in facilitating green marketing implementation, analyze its impact on market share expansion, with a specific focus on the Micro, Small, and Medium Enterprises (MSMEs) sector, and critically evaluate the environmental challenges stemming from digital technology adoption. The methodology employed is a systematic literature review, utilizing data extraction from four reputable academic databases: Scopus, Web of Science, Google Scholar, and IEEE Xplore. Based on inclusion criteria restricted to English-language peer-reviewed articles, the final selection process yielded 82 relevant studies for analysis. The findings indicate that the integration of digital payment platforms and artificial intelligence (AI) significantly enhances market reach, operational efficiency, and the personalization of marketing campaigns. Furthermore, FinTech has been shown to facilitate the provision of green investment infrastructure, carbon footprint tracking, and incentives for eco-friendly transactions.